K-Means Cluster Analysis for District or City Clustering in Bengkulu Province based on The Number of Base Transceiver Stations and The Strength of Cell Phone Signal - Anisa Rahmawati; Endah Setyowati (CESS (Journal of Computer Engineering, System and Science), 2023)
The existence of a Base Transceiver Station (BTS) and the strength of cell phone signals in an area have greatly affected the ease of communication and exchanging information between people. This is one aspect to measure technological developments in a region. This study aims to use the K-Means algorithm to classify districts or cities in Bengkulu Province based on the proportion of BTS presence, the proportion of villages with strong telephone signals, and the proportion of villages with 4G internet signals. There are three clusters based on these three variables and there are still significant differences between districts or cities in Bengkulu Province. The output of this study becomes an input for the Bengkulu provincial government to be able to pay attention to the distribution of communication infrastructures in their province.